FRI0350 Quality of life of juvenile idiopathic arthritis cohort at adulthood in a transition program. (23rd January 2014) - Sparsa, L.; Job Deslandre, C.; Quartier, P.; Kahan, A.; Wipff, J.
Abstract : Background: Health Related Quality of Life (HRQoL) is affected in Juvenile idiopathic arthritis (JIA) because of pain, functional impairment and joint destruction. The main quality of life score used in JIA is the C-HAQ (Child Health Assessment Questionnary), pediatric version of HAQ (Health Assessment Questionnary) used for adult. Transition of care includes a transfer from paediatric to adult health care. No previous specific evaluation of HRQoL had already been performed in this particular transitional period. Objectives: In our study, we propose to determine the impact of JIA on QOL in a large transition JIA cohort and to evaluate which HRQoL questionnaire should be used in practice. Methods: All consecutive patients with AJI followed during adulthood in a transition care program at Cochin Hospital were included. Demographics, clinicals and biologicals datas have been collected: tenderness and swelling joints (respectively TJS, SJS), decrease of joint mobility (LOM), visual analigic scale (VAS) of pain, activity and physician, erythrocyte sediment rate (ESR), CRP and currently therapy. Quality of life questionnary given were: CHAQ child and parent versions, HAQ, SF-36 and EuroQol. Results: 121 JIA were included (82 women and 29 men). The mean age was 19.9±3.7 years [8-34]. The mean age at the diagnosis was 8.6±5.2. The mean age at the first symptom was 8.4±5 years [1-20] while the diagnosis was made nearly 28 months later. Sub-types of JIA were as followed: 44 oligoarthritis, 28 ERA, 5 psoriasic arthritis, 27 polyarticular form and 17 with systemic JIA. 58/121 (48%) are treated by biotherapy and 43/121 (36%) were considered in remission. CHAQ child and parents were respectively 0.6±0.6 and 0.6±0.7. The mean HAQ was 0.5±0.6. There is a strong correlation between CHAQ and HAQ (r=0.93, p<0.0001). Both questionnaires were also correlated with pain, global and physician VAS and with remission. CHAQ and HAQ were higher in polyarticular subsets compared to other sub-groups of JIA whereas pain and global VAS were higher in ERA group. Results of SF36 showed that JIA had more impact on physical status (PCS=41.8±10) than on mental status (MCS=46.5±11.7). EuroQOL results confirm this result: only 26% had no pain/discomfort compared to 59% for absence of anxiety/depression. The only difference between sub-types of JIA is a better mental status of patients with systemic JIA compared to other groups. Global health status assessments by EuroQOL, PCS, MCS are closely correlated with each other and for specific physical and mental part of these questionnaires. They were also and negatively correlated with Steinbrocker classification, as expected. Conclusions: Evaluation of HRQoL in a large transition cohort of JIA patients at adulthood showed that JIA has a moderate impact on quality of life. JIA has more physical consequences compared to mental status of patients. His functional consequence could be evaluated by either HAQ or CHAQ but HAQ seems to be simpler and age-appropriate in practice. Mental status is evaluated in the same way by SF-36 or EuroQOL allowing the use of one or the other indifferently. Disclosure of Interest: None Declared